Land market regulations in Europe - Johan Swinnen; Kristine Van Herck; Liesbet Vranken (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2014)
Land regulations have a major impact on economic development, especially in agrarian societies, and they continue to affect the efficiency of the rural economy when economies further develop. This paper aims to give an overview of the regulations that are present in the land market in the EU member states and builds a land regulatory index to quantify the extent of regulations of agricultural land sales and rental markets.
Keywords: 330; institutions; regulation; land markets; Europe